Analysis of Agroindustry Development Strategy: A Case Study at CV Andi Jaya Sumbersuci - Aniqurroziqi, Ashef; Andriani, Nurita; Ansori, Mochammad (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Processing Coconut into Coconut Oil at CV. Andi Jaya is a company that operates in the field of processing Coconut into Coconut Oil. To achieve growth and success in its business, companies use SWOT analysis. The company plans the growth of coconut oil production by identifying specific and ambitious production targets within a certain period. So that CV. Andi Jaya can allocate resources wisely and direct operations to achieve the goals set by the company using strategic maneuvers in marketing and distributing its products. Through effective promotional strategies and collaboration with business partners, CV. Andi Jaya is able to increase product visibility and achieve and increase sales. CV. Andi Jaya periodically analyzes production growth patterns and market demand, by understanding these patterns the company can adjust production and product inventory to optimize efficiency and increase customer satisfaction. The company is trying to strengthen its position in the market as a producer of crude coconut oil by maintaining quality standards and content, CV. Andi Jaya creates customer trust and wins a larger market. The company prioritizes optimal use of raw materials and presents environmentally friendly products, thereby supporting a sustainable environment.